Strengthening Pandemic Preparedness in Undergraduate Education through Curricular Reform: Post-COVID-19 Insights - Dea Goderdzishvili; Elza Nikoleishvili (European Scientific Journal, ESJ, 2025)
Aims and Scope: The COVID-19 pandemic exposed widespread gaps in undergraduate biomedical and health sciences programs' ability to prepare future healthcare professionals for public health emergencies. This study aimed to identify key curricular indicators for strengthening pandemic preparedness in undergraduate education, using Georgia as a representative case study of a resource-constrained setting. Methods: A qualitative study was conducted using virtual semi-structured interviews with 33 educators recruited through purposive sampling based on teaching experience and disciplinary background. Participants represented medicine, public health, nursing, dentistry, and pharmacy programs - 30 from Georgian institutions and 3 international experts for data triangulation. Data collected from May to August 2024 were analysed using inductive thematic analysis in MAXQDA, a qualitative analysis software. Ethical approval was obtained from The University of Georgia School of Health Sciences Ethics Committee (Approval Number: N:11-6461). Findings: Three key curricular indicators emerged for strengthening pandemic preparedness: (1) institutional readiness by embedding pandemic-focused content and simulation-based learning into core curricula; (2) public health communication, including vaccine advocacy, crisis response messaging, and risk communication; (3) research and collaboration capacity through interdisciplinary and international engagement to build a responsive academic workforce. Conclusion: Despite lessons from COVID-19, many undergraduate biomedical and health sciences programs continue to lack structured disaster preparedness instruction, leaving students unprepared for emergency response. The identified key indicators provide a foundation for undergraduate curricular reform. Using Georgia as an example, the findings present a scalable reform framework to strengthen pandemic preparedness, system resilience and better prepare future professionals for public health emergencies.